Brain complications of diabetes mellitus: a cross‐sectional study of awareness among individuals with diabetes and the general population in Ireland. Issue 7 (2nd May 2018) - Dolan, C.; Glynn, R.; Griffin, S.; Conroy, C.; Loftus, C.; Wiehe, P. C.; Healy, M. L.; Lawlor, B.
Abstract: Aims: To identify awareness of potential brain complications of diabetes among individuals with diabetes and the public. Methods: For this observational, cross‐sectional survey study, we recruited consecutive adult attendees of a specialist diabetes clinic and two primary care practices. Primary care attendees represented members of the general population of Ireland. An interviewer‐administered questionnaire was used to gather data on respondents' awareness of brain complications of diabetes and modifiable risk factors for dementia. Multivariable logistic regression was undertaken to identify variables independently associated with awareness. Results: Respondents included a total of 502 adults: 250 in the diabetes group (37% women, mean age 63 ± 14 years, 88% with Type 2 diabetes) and 252 in the general population group (51% women, mean age 47 ± 17 years, 7% with Type 2 diabetes). The diabetes group had significantly greater awareness of diabetes complications, except for depression, compared with the general population group. In the group as a whole, respondent awareness of dementia (35%) and memory problems (47%) as potential complications of diabetes was poor compared with awareness of kidney (84%) and eye damage (84%). Respondents were 1.5 times more likely to identify that individuals can modify their risk of developing Type 2 diabetes than their risk of dementia. Conclusions: This study shows that there is poor awareness of brain complications of diabetes among individuals with diabetes and the general population in Ireland. The results suggest a need for expansion of public awareness campaigns and diabetes education programmes to promote awareness of the brain complications of diabetes and of the modifiable risk factors for dementia, as part of a life‐course approach to dementia prevention. What's new?: Awareness of the brain as vulnerable to adverse effects of diabetes including dementia is growing among the research community, but research exploring associated awareness among individuals with diabetes and the general public is lacking. Using data from more than 500 survey respondents, we found that awareness of brain complications of diabetes was significantly lower than awareness of other organ complications. Knowledge of modifiable risk factors for dementia was also poor. The study results point to the need to increase public awareness of the link between dementia and diabetes and highlight that diabetes is a potentially modifiable risk factor for dementia.